Blood pressure control with cilnidipine treatment in Japanese post-stroke hypertensive patients: The CA-ATTEND study. (3rd April 2017) - Aoki, Shiro; Hosomi, Naohisa; Nezu, Tomohisa; Teshima, Tsukasa; Sugii, Hitoshi; Nagahama, Shinobu; Kurose, Yoshiki; Maruyama, Hirofumi; Matsumoto, Masayasu
ABSTRACT: Blood pressure control is important in post-stroke hypertensive patients and antihypertensive treatment is recommended for such patients. Ca-channel blockers are recommended as the medications of choice for the treatment of post-stroke patients. Here, we report the results of a large-scale prospective post-marketing surveillance study of post-stroke hypertensive patients ( n = 2667, male 60.4%, 69.0 ± 10.9 years) treated with cilnidipine, with regard to blood pressure control and adverse reactions. Cilnidipine treatment caused a decrease in both clinic and home blood pressures 2 months after the beginning of treatment, and the decreased blood pressure was maintained until the end of 12 months' observation. The proportion of patients in whom clinic blood pressure was well controlled (<140/90 mmHg) increased from 21.5% to 65.3% in cilnidipine treatment, with no differences in effectiveness among the various clinical subtypes of stroke. In total, 346 adverse events occurred, with an overall incidence of 8.9% (238 of 2667 patients). In the elderly group, specifically, a fall and a hip fracture each occurred in 1 (0.1%) patient. These results indicate that cilnidipine was effective in treating uncontrolled blood pressure and was well tolerated in Japanese post-stroke hypertensive patients in a real-world clinical setting.